ANALISIS KINERJA KEUANGAN DENGAN PENDEKATAN ECONOMIC VALUE ADDED (EVA) PADA PERUSAHAAN YANG TERDAFTAR PADA JII TAHUN 2021 - Jilma Dewi AyuNingtyas; Pratomo Cahyo Kurniawan (ECONBANK: Journal of Economics and Banking, 2022)
This research will focus on analyzing the company's financial performance using the EVA approach on Islamic stocks indexed at JII in 2021. This research uses a descriptive quantitative approach with a population of financial statements of companies listed on the Jakarta Islamix Index (JII) in 2021. For analysis financial report data using the economic value added (EVA) approach, preceded by calculating the variables from EVA. The variables consist of NOPAT (net Operating after tax), Invested capital (invested capital), WACC (weighted average cost of capital), capital charger (cost of capital), then calculate EVA (economic value added). Based on the results of the research, it can be concluded that, 1) companies listed on the JII index in 2021 are divided into two groups, namely companies whose company value is GOOD as seen from the positive EVA value and the category of companies whose company value is LESS with negative EVA value. 2) if the calculation of the value of NOPAT, Invested capital, WACC / weighted average cost of capital, and Capital charges is positive, the EVA value will also be positive. capital, and Capital charges are negative, the EVA value is also negative.